PERSAINGAN INDUSTRI RITEL DI INDONESIA DENGAN MODEL â€LIMA KEKUATAN PESAING M. PORTERâ€ - Mawardi, Mukhammad Kholid (IQTISHODUNA, 2008)
The most disruptive competition industry in Indonesian business is retail industry, having significant role in value chain management of product distribution from producers to consumers. To asess retailÂ  industry competition in Indonesia writer use the five force model introduced by Michael Porter. This model is the implementation of S-C-P (Structure-Conduct-Performance) paradigm in industries asessment. This articlesÂ  concluded that retail industry in Indonesia is attractive and long- lasting industryÂ